INFLUENCE OF GROWTH REGULATORS ON OVULES ABORTION, SEED SET AND ITS GERMENATION OF TWO ALFALFA CULTIVARS - & Al-Beiruty, Khrbeet (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
A field experiment was conducted at the experimental farm, College of Agriculture, Abu-Ghraib, Baghdad, Iraq during the period from mid. of March 2012 to mid. of July 2014 to investigate the effects of plant growth regulators and foliar application stages on ovules abortion, seed set and its germination of two alfalfa cultivars. Layout of the experiment was R.C.B.D. arranged in split-split plot with three replications. Cultivars (local and hamedan) were assigned as a main plot and foliar application stages (vegetative growth, flower buds emergence, 50% flowering and 80% flowering) were assigned as sub-plots, while growth regulators (Alar, Ethephon, Naphthalene acetic acid(NAA) and control treatment) were assigned in the sub-sub-plots. Result showed that there were no significant differences between cultivars in all traits. Foliar application of NAA increased No. of ovules per floret (9.11) compare with other treatments, but it was not significantly different compare with Alar. In 1st and 2nd seed crop, plants sprayed with Alar at flower buds emergence stage gave highest seed set (5.17, 6.93) respectively. Percentage of ovules abortion significantly influenced by growth regulaters, folair application stages and their interaction. Since, foliar application of Alar at beginning of flower buds emergence reduce % of ovules abortion (30.89). In general, plants sprayed at vegetation growth stage increased % of seed germination. It was clear from this study that more than 40% of ovules were aborted, this may be one of the reasons for reduction of seed yield in alfalfa, therefore, we recommended to do more researches in this field in order to know the causes of ovules abortion.